(untitled) (MAUSAM, 1960)
The East-West component microseisms recorded at the Indian Naval Physical Laboratory, Cochin during the September 1959 cyclone in the Bay of Bengal; have been studied. A new technique of analyzing the data using the band-pass filter has been adopted. This method makes it possible to separate out the local short-period microseisms and distant storm microseisms. Intensity of 2-5 seconds microseisms shows good correlation with the formation, intensification and movement of the cyclone.